Flexible endosopic management of Zenker's diverticulum: characteristics and outcomes of 52 cases at a tertiary referral center. Issue 3 (24th February 2015) - Halland, M.; Grooteman, K. V.; Baron, T. H.
Summary: Zenker's diverticulum causes substantial morbidity among affected elderly patients. In the United States, rigid endoscopic cricopharyngeal myotomy is the mainstay of management and the flexible endoscopic technique is reserved for those not deemed candidates for rigid endoscopy due to an inability to extend the neck and/or medical comorbidities. Short‐ and long‐term outcomes following flexible endoscopic cricopharyngeal myotomy in the United States are limited. We reviewed the patient characteristics and outcomes of 58 consecutive flexible endoscopic cricopharyngeal myotomies performed at Mayo Clinic, Rochester, between March 2006 and November 2013. There were 58 procedures performed on 52 unique patients. The median age was 77 years, and 48% of patients were female. More than one third of patients had either failed previous rigid therapy or were deemed inoperable by the referring surgeon. Size of the diverticulum ranged from 1 cm to 5 cm with a mean of 2.8 cm. Most procedures (67%) were performed under general anesthesia. Initial procedural success was achieved in all patients. Of the patients, 77% reported complete symptom resolution at mean follow‐up time of 26 months. Of the procedures, 71% were not associated with any adverse event, but esophageal microperforation occurred during 11 procedures (19%). Of these, nine resolved with conservative management, one required an endoscopic stent, and one developed a neck abscess that required drainage. Our data show in a group of elderly patients with preexisting comorbidities flexible endoscopy therapy for Zenker's diverticulum is feasible. Initial symptomatic improvement was universal, and long‐term response appears durable. The most common adverse event was esophageal microperforation, and the majority (82%) of these resolved with conservative management. Direct comparison with outcomes of rigid endoscopic or open surgical techniques has not been performed, but these data suggest that a randomized trial is warranted to assess the efficacy and safety of a flexible endoscopic technique.